A burgonya alternatív és herbicides gyomszabályozási technológiáinak vizsgálata - Dezső, Dániel; Pásztor, György (GEORGIKON FOR AGRICULTURE, 2022)
In our experiment we compared the effect of organic mulch (wheat strew and grass mulch) on the weed cover, yield and quality of potatoes, with some herbicides. Early in the vegetation period the grass mulch and strew had very good weed suppression (2-5% weed cover), but lately in the end of the vegetation this suppression decreased, especially in the grass mulch (46.9-65.6% weed cover), so they had not good enough effect against the weeds (14.3 - 15.14 t/ha yield was occurred). However, preemergent applicated S-metolachlor and metribuzin gained good effect. The individually used pendimethalin did not had significant effect on weed cover, yield or other examined parameters compared to the weedy check, furthermore its effect on the weed Lolium multiflorum was very low, that can signal the resistance of the weed species on the pendimethalin.
Keywords: potato; weed control; mulch; strew; grass mulch; metribuzin; pendimethalin